Juvenile growth in barnacles: combined effect of delayed metamorphosis and sub-lethal exposure of cyprids to low-salinity stress. - Pechenik, Jan A.; Thiyagarajan, Vengatesen.; Gosselin, Louis André.; Qian, Pei-Yuan. (Tufts University. Tisch Library., 2017)
Delayed metamorphosis can affect post-metamorphic performance in a variety of marine invertebrate species, possibly through effects on larval energy reserves. Nevertheless, the consequences of the 'latent effects' of natural environmental conditions and the proximate causes of the effects have rarely been examined. We documented the combined effect of delayed metamorphosis and sub-lethal exposure of larvae to low-salinity stress on depletion of energy reserves, metamorphic success and juvenile growth rates for the estuarine barnacle Balanus amphitrite, both in the laboratory and in field outplant experiments. Acute (24 h) exposure of 0 d old cyprids to low salinity (10 psu) dramatically reduced juvenile growth rates (measured as basal diameter, dry weight and ash-free dry weight) for the first 5 d after metamorphosis, in both laboratory and field conditions, and the effects were similar to those resulting from delayed metamorphosis. There was an interaction between delayed metamorphosis and salinity effects on juvenile tissue growth rates. To determine how the negative effects of delayed metamorphosis observed in the laboratory might be modulated in the field under different nutrient conditions, we also outplanted juveniles from cyprids that had delayed metamorphosis for either 0 d (control) or 4 d at 2 intertidal sites that experienced different nutrient conditions. Surprisingly, surplus food availability in the juvenile habitat could not entirely compensate for the negative effects imposed by delayed metamorphosis on juvenile growth rates. Additionally, we examined whether or not the detrimental effects of delayed metamorphosis on growth were mediated through effects on juvenile feeding rates and feeding appendage (cirri) morphology. Interestingly, although 2 out of the 3 juvenile feeding cirri lengths were shorter than expected in delayed individuals, mean juvenile filtration rate was significantly higher in delayed individuals than in control individuals. Overall, our results emphasise that acute exposure of competent larvae to low-salinity stress negatively affects juvenile growth rates as severely as delayed metamorphosis, which may ultimately influence juvenile and adult population dynamics in the field. The cause of reduced post-metamorphic performance in young barnacles remains unclear, but does not seem to be caused by reduced capacity for feeding.